2020
DOI: 10.1093/gbe/evaa016
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a New TLR Gene and Gene Expansion Event through Improved Desert Tortoise Genome Assembly with Chromosome-Scale Scaffolds

Abstract: Abstract Toll-like receptors (TLRs) are a complex family of innate immune genes that are well characterized in mammals and birds but less well understood in nonavian sauropsids (reptiles). The advent of highly contiguous draft genomes of nonmodel organisms enables study of such gene families through analysis of synteny and sequence identity. Here, we analyze TLR genes from the genomes of 22 tetrapod species. Findings reveal a TLR8 gene expansion in crocodilians a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Gene duplication events can facilitate the evolution and expansion of a gene family's function, specialized sub-functionalization, or differences in gene expression [175][176][177]. However, gene loss through mutations or pseudogenization can also be an adaptive evolutionary force depending on gene dispensability, mutational robustness, and environmental conditions [178]. The genomic diversity of TLRs in non-model species is a very interesting area of research, indicating evolution through both positive and negative selection because of infectious or environmental pressure.…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…Gene duplication events can facilitate the evolution and expansion of a gene family's function, specialized sub-functionalization, or differences in gene expression [175][176][177]. However, gene loss through mutations or pseudogenization can also be an adaptive evolutionary force depending on gene dispensability, mutational robustness, and environmental conditions [178]. The genomic diversity of TLRs in non-model species is a very interesting area of research, indicating evolution through both positive and negative selection because of infectious or environmental pressure.…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…Indeed, we found many general immune-related responses to be enriched among experimental immune groups, including GO:0002275 (myeloid cell activation involved in immune response), GO:0009410 (response to xenobiotic stimulus), and GO:0002252 (immune effector process). Previous studies on turtles revealed expression of immune-related genes [2,31,38,[58][59][60][61][62][63]] associated with both innate and adaptive immune functions. We expected differential expression of cytokines (e.g.…”
Section: Plos Onementioning
confidence: 99%
“…Yet, the hybrid zone between these species indicates they have not yet reached complete reproductive isolation, offering an opportunity to assess to what degree genomic reinforcement mechanisms have developed in this lineage pair. To do this we developed a chromosome-scale reference genome for G. morafkai and performed comparative genomic analyses with the published reference genome for G. agassizii 23 .…”
Section: Introductionmentioning
confidence: 99%